2016
DOI: 10.1111/cea.12708
|View full text |Cite
|
Sign up to set email alerts
|

Ranitidine‐induced anaphylaxis: clinical features, cross‐reactivity, and skin testing

Abstract: Although ranitidine is known as a safe drug, it can also cause diverse adverse reactions, including anaphylaxis. This study demonstrates the need to pay attention to adverse reactions to ranitidine and consider ranitidine as a cause of anaphylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…Records of hypotension as an adverse event (AE) and any types of AEs to be associated with propacetamol or paracetamol were collected from 27 pharmacovigilance centers involved in the Korea Institute of Drug Safety (KIDS)–Korea Adverse Event Reporting System (KAERS) from 2011 to 2014 . All of the regional pharmacovigilance centers participating in the KAERS database collect and evaluate ADRs in accordance with instructions provided by the KIDS.…”
Section: Methodsmentioning
confidence: 99%
“…Records of hypotension as an adverse event (AE) and any types of AEs to be associated with propacetamol or paracetamol were collected from 27 pharmacovigilance centers involved in the Korea Institute of Drug Safety (KIDS)–Korea Adverse Event Reporting System (KAERS) from 2011 to 2014 . All of the regional pharmacovigilance centers participating in the KAERS database collect and evaluate ADRs in accordance with instructions provided by the KIDS.…”
Section: Methodsmentioning
confidence: 99%
“…In a study evaluating 584 patients (694 cases) with ADRs caused by ranitidine, anaphylaxis was occasionally observed. 69 Besides, ranitidine metabolite from several manufacturers has been reported to have a carcinogenic property in September 2019, then, many drugs including ranitidine have been withdrawn from the market. Thus, while short-term use of H 2 RAs may be indicated in the management of FD, caution may need to be taken.…”
Section: Acid Suppressantsmentioning
confidence: 99%
“…This supports international recommendations to consider repeat allergy testing in patients with a high likelihood of drug allergy (at least for beta‐lactam allergy), including drug provocation testing, even if they pass the initial challenge test . Park et al highlighted ranitidine as a cause of anaphylaxis, which in their experience was often overlooked due to the presumption that this drug is not a common cause of allergic reactions; however, the authors report on 584 cases, including 99 with anaphylaxis. Another significant cause of drug allergy is chlorhexidine; Opstrup et al found that most patients with chlorhexidine allergy have positive specific IgE 1 to 4 months postreaction and that although specific IgE declines after this time, this does not necessarily mean the drug allergy has resolved, with cases recorded of recurrent reaction years later despite negative specific IgE.…”
Section: Clinical Allergymentioning
confidence: 75%